GSTO1C/GSTO2G haplotype is associated with risk of transitional cell carcinoma of urinary bladder - Djukic, Tatjana; Simic, Tatjana; Radic, Tanja; Matic, Marija; Pljesa-Ercegovac, Marija; Suvakov, Sonja; Coric, Vesna; Pekmezovic, Tatjana; Novakovic, Ivana; Dragicevic, Dejan; Savic-Radojevic, Ana (International urology and nephrology, 2015)
Purpose To clarify the role of genetic polymorphisms of GSTO1 (rs4925) and GSTO2 (rs156697) in individual susceptibility to urinary bladder cancer. Methods Case–control study consisting of 187 patients with histologically confirmed transitional cell carcinoma (TCC) of urinary bladder and 140 age- and gender-matched cancer-free controls was carried out. Genotyping of GSTO1 and GSTO2 was performed by polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP). Results We found that carriers of mutant GSTO2 *G/G genotype were at increased risk of the development of TCC (OR 2.6, 95 % CI 1.2–5.8, p = 0.041), while GSTO1 rs4925 polymorphism was not significantly associated with TCC risk ( p = 0.450). According to smoking status, smokers with GSTO2 *G/G genotype had significantly higher risk of TCC of urinary bladder (OR 4.3, 95 % CI 1.6–11.2, p = 0.003) compared to wild-type carriers with no smoking history. We further analyzed the effects of GSTO1 / GSTO2 haplotypes on TCC risk, based on the linkage disequilibrium found for GSTO1 (rs4925) and GSTO2 (rs156697) ( D ′ = 0.309, p = 0.001). The study subjects with GSTO1 *C/ GSTO2 *G ( GSTO1 wild-type/ GSTO2 mutant) haplotype were at the highest risk of the development of transitional cell carcinoma of urinary bladder (OR 2.8, 95 % CI 1.5–5.2, p = 0.002). Conclusions Our results indicate that GSTO1 *C/ GSTO2 *G haplotype is associated with increased risk of TCC. The modifying effect of GSTO2 *G/G genotype on individual susceptibility to TCC is more pronounced, when associated with smoking.